The Effect of Hypnosis on Pain Management in Cancer Patients: A Systematic Review - Harahap, Ikhsanuddin Ahmad (Caring: Indonesian Journal of Nursing Science, 2024)
This review article aimed to find current evidence about the effect of hypnosis in reducing pain in cancer patients. The titles and abstracts of relevant articles were reviewed on digital databases, including PubMed, ScienceDirect, and ProQuest, between 2016 and 2021 (last 5 years) using the search terms hypnosis AND cancer pain. The inclusion criteria for this review included English-language research articles with either a Randomized Control Trial, Non-Randomized Trial, experimental design, or case-control with full-text access to a population of cancer patients with hypnosis intervention, and the output was pain. The reviewer has independently evaluated 5 articles; 3 have a Randomized Control Trial design, and 2 are Non-Randomized Trials. The pain was measured using PNRS, VAS, and the combination of PNRS-VAS. 3 articles stated that hypnosis was significantly different between groups in terms of pain, and 2 articles stated no significant difference. In addition, hypnosis therapy also has a beneficial effect on inhibiting all cancer modalities. Different hypnosis methods are used.